1998
DOI: 10.1063/1.366764
|View full text |Cite
|
Sign up to set email alerts
|

Optimum doping level in a-Si:H and a-SiC:H materials

Abstract: The changes in the optical and electrical properties of thick a-Si:H and a-SiC:H films doped with diborane are investigated. In situ spectroscopic ellipsometry measurements reveal that, at a ratio of diborane to silane Cg=[B2H6]/[SiH4]<10−3, the optical properties of both materials are not strongly modified by boron doping. However, in the case of a-Si:H films, an improvement of the morphological and optical properties is observed at Cg=0.45×10−3. The existence of an optimum doping level at Cg<10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
5
17
1
Order By: Relevance
“…They attributed that to the increased material density and to the decreased hydrogen concentration of the film. 16 The results from Hadjadj et al 16 are in agreement with our results, showing that an increased hydrogen content in the film lowers the refractive index. This is probably due to both the passivation of dangling bonds and a decrease in the film density.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…They attributed that to the increased material density and to the decreased hydrogen concentration of the film. 16 The results from Hadjadj et al 16 are in agreement with our results, showing that an increased hydrogen content in the film lowers the refractive index. This is probably due to both the passivation of dangling bonds and a decrease in the film density.…”
supporting
confidence: 83%
“…They attributed the reduced refractive index to the increased internal strain. However, Hadjadj et al 16 found that the refractive index increased strongly for boron doping concentrations above 10 [B 2 H 6 ]/[SiH 4 ]. They attributed that to the increased material density and to the decreased hydrogen concentration of the film.…”
mentioning
confidence: 99%
“…The slope of the valence band tail E OV (see Table 1), which is an indicator of disorder in the material, is higher for the doped a-SiC:H films than for the doped a-Si:H. In our previous paper [1] the poorer morphology of the aSiC:H alloys compared to the a-Si:H and the smaller effect of the boron doping on their properties was discussed. These results are in very good agreement with the microhardness measurements.…”
Section: Discussionmentioning
confidence: 96%
“…Boron doped a-Si:H and a-SiC:H, 0.54-0.68 lm thick films were deposited on Corning glass substrates at 180°C by RF glow discharge decomposition of 10 sccm of silane mixed with either diboran or trimethylboron diluted at 2% in hydrogen [1,2]. The boron doped silicon-carbon alloys (a-SiC:H) usually used as window layers in solar cells were produced by the decomposition of the mixture of 50% silane and methane.…”
Section: Methodsmentioning
confidence: 99%
“…The Si-O-Si bridge has a stronger bond energy compared to the Si-Si bond energy due to either a decrease in the band width or an increase in the energy difference between bonding and anti-bonding splitting regarding Si-Si derived bonds [12]. The bond energies for the Si-O bond in SiO 2 and the Si-Si bond in c-Si appears to be 4.8 eV and 2.3 eV, respectively [13]. The B 2 H 6 often attributed to the increase of disorder in the network and the removal of oxygen from the p-type a-SiO x :H films.…”
Section: Results and Dicussionmentioning
confidence: 99%